Produksi Film Pendek “In Solo” Berbasis Multimedia - Indra Irawan (APMMI - Asosiasi Profesi Multimedia Indonesia, 2014)
ABSTRACT : The development of cinema at the University of Surakarta now had enough amount with the theme of the movie is varied, there are themed documentary, romance, education, and others. Movie called